Langkah Strategis Transformasi Pendidikan Islam di Era Globalisasi - Nadir; Januar (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2024)
This article discusses the importance of strategic thinking and action in Islamic education to maintain its relevance in the challenging era of globalization. Islamic education, which aims to form moral and knowledgeable human beings, must be able to adapt to technological developments and rapid social changes. The novelty of this article lies in identifying strategic measures to improve the quality of Islamic education, such as the formulation of an adaptive vision and mission, curriculum innovation, development of teaching staff, and collaboration with various parties. Using the literature research method, this article compiles a review of the literature and content analysis to understand the necessary transformation of Islamic education. The results show that a structured strategy can enhance the role of Islamic education in shaping a competitive and moral generation. In conclusion, Islamic education that integrates Islamic values with modern approaches has great potential to support the advancement of Muslim civilization in the global era.